L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Optimizing mass rearing and field release of Telenomus remus for effective biological control of Spodoptera litura - De-Rui Han; Guang Zou; Chao-Zhou Liu; Xia Wen; Xiao-Fei Yu; Mao-Fa Yang; Guy Smagghe; Jian-Feng Liu; Chun-Yang Huang (Crop Protection, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

The role of continental and oceanic subduction in generating the giant Jiaodong gold province, China: Constraints from mercury isotopes - Hong Wang; Ting-Guang Lan; Yang Xu; Hong-Rui Fan; Huan-Long Hu; Lei Shu; Lang‑Ye Zhao; Xing-Hui Li (Gondwana Research, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Decoupling between sediment immobilization and modeled ecological risk of emerging metals in coastal mariculture sediments - Yang-Guang Gu; Yanpeng Gao; Rui-Ze Liang; Richard W. Jordan; Shi-Jun Jiang (Marine Pollution Bulletin, 2026)

How plant diversity and nitrogen deposition affect the net nutrient retention on temperate extensive green roofs: A case study - Guang Hao; Yihan Wang; Hechen Li; Shaobo Gao; Runze Wu; Zhuolin Li; Jiale Han; Hongyuan Li; Rui Hua; Nan Yang (Ecological Engineering, 2026)

High-throughput prediction of the lowest triplet excitation energies in organic photovoltaic acceptors using physics-guided excess-factor-corrected fragment descriptors - Lei Cheng; Rui-Cheng Qin; Peng Xie; Ming-Yang Li; Yue Ren; Guang-Yan Sun (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Underground mine tunnel fire dynamics: Experimental investigation and AI-driven characterization of flame behavior - Jingmin Xu; Rui Tian; Ashish Kakoria; Aamir Iqbal; Tao Yang; Lina Zheng; Guang Xu (Tunnelling and Underground Space Technology, 2026)

Effects of Alhagi sparsifolia root content and soil moisture content on soil deformation and strength under different freeze-thaw temperature conditions - Meixue Zhang; Qinglin Li; Xuanbing Luo; Wenjuan Chen; Rui Wang; Shuailong Yu; Guang Yang (Soil and Tillage Research, 2026)

Microbial inoculation in green roofs: progress, challenges and ecological regulation strategies - Nan Yang; Hechen Li; Yihan Wang; Pingrui Jiang; Shaobo Gao; Hongyuan Li; Rui Hua; Xinjian Shi; Guang Hao (Urban Ecosystems, 2026)

Excavation Damage Evaluation of Rock Anchor Beam Based on Acoustic P-Wave Velocity and RFD Index in Highly Stressed Powerhouse: A Case Study of Baihetan Hydropower Station, China - Jin-Shuai Zhao; Lei Xia; Yong Fan; Quan Jiang; Bing-Rui Chen; Guang-Dong Yang; Dong-Ze Wang (Rock Mechanics and Rock Engineering, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Zircon thermal annealing ages determine a late Eocene birth for the First Bend of the Yangtze River - Yang Zhang; Rui Li; Guang-Yan Zhou; David Chew; Jian-Ping Zheng; Qing Xiong; Wei Wang (Earth and Planetary Science Letters, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Design of BDS-3 signal distortion bias model and analysis of its performance - Saisai Gao; Ran Li; Jiatong Wu; Xiaoyun Wan; Rui Guo; Xiaojie Li; Shanshi Zhou; Guang Yang (Advances in Space Research, 2026)

Unravelling the antifungal mechanism of phytic acid on Aspergillus flavus development and aflatoxin B1 biosynthesis - Guang Yang; Shuwen Li; Jingrong Liu; Huayan Wang; Rui Hong; Yimei Zhang; Andong Gong (Food Additives & Contaminants: Part A, 2026)

Grazing disturbance reduces soil organic carbon sequestration and stability in desert steppe - Naijing Lu; Tianqi Zhao; Jianying Guo; Mengli Zhao; Guodong Han; Zhongwu Wang; Jiangfeng He; Rui Zhao; Yong Wang; Jian Guan; Bin Zhang; Guang Yang (Journal of Environmental Management, 2025)

Effect of turbulence induced shear on continuous synthesis of imidazolium ionic liquid 1-butyl-3-methylimidazolium bromide ([BMIM]Br) in a high shear rate Taylor-Couette flow reactor - Rui Jiang; Guang Li; Bin Li; Yanhong Guo; Xiaogang Yang (Chemical Engineering Journal, 2025)

CFD–DEM and Experimental Investigation of Seepage Behavior at Soil–Structure Interfaces - Xue-min Yang; Zeng-guang Xu; Jun-rui Chai; Cheng Cao; Chao-wei Sun; Gang Li (Geotechnical and Geological Engineering, 2025)

A novel upcycling process of polystyrene wastes into benzaldehyde by catalyst-free laser flash depolymerization and in-line oxidation - Fu-Lu Chang; Lun Chen; Bin Hu; Fu-Rui Chen; Han Yang; Guang-Jian He (Chemical Engineering Journal, 2025)

Spatiotemporal evolution and driver analysis of wastewater greenhouse gas emissions in Chinese mainland: Insights and future trends - Yang Chen; Rui Qiu; Min Zheng; Bing-Jie Ni; Hong-Guang Guo (Environmental Research, 2025)

Determination of metal(loid) bioavailability in peri-urban agricultural soils and sediments of Southeast China by DGT and probabilistic risk assessment of DGT-derived data - Xihe Yue; Rui-Ze Liang; Richard W. Jordan; Hong Su; Shi-Jun Jiang; Yang-Guang Gu (Journal of Soils and Sediments, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Upcycling of cathode materials from spent lithium-ion batteries cathode materials enabled by deep eutectic solvent - Yanshun Liao; Xianglei Meng; Hongwei Wu; Guang Yang; Xinyao Zhang; Rui Tang; Yali Li; Ni Yang; Yibiao Guan; Yuefeng Su; Feng Wu; Qing Huang (Journal of Environmental Chemical Engineering, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate inflammatory pain by downregulating the expression of P2Y14 receptor in the primary somatosensory cortex - Shuai Hou; Cui-Yuan Chen; Rui-Zhu Zhou; Liu-Xuan He; Xiao-Xiao Zhao; Sha-Sha Chen; Sha Yang; Hai-Yan Yin; Shu-Guang Yu (Purinergic Signalling, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Coastal redox shifts over the past 167 years and preservation of total organic carbon and total nitrogen - Yang-Guang Gu; Hai-Song Li; Hong Su; Richard W. Jordan; Rui-Ze Liang; Shi-Jun Jiang (Marine Pollution Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Synergistic improvements of properties of cellulose acetate based curcumin@TiO2 nanofibers via triaxial electrospinning - Wenbin Deng; Yu Liu; Cui He; Xiaozhou Xiong; Rui Zhang; Tingfei Yan; Shuichao Shi; Deng-Guang Yu; Haisong Yang (Chemical Engineering Journal, 2025)

The source and dissemination of ARGs in pristine environments: Elucidating the role of migratory birds in the Arctic - Qin Shu; Hui Gao; Rui-jing Li; Hai-yang Chen; Guang-shui Na (Journal of Hazardous Materials, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Pollution concerns in mariculture water and cultured economical bivalves: Occurrence of microplastics under different aquaculture modes - Kexin Song; Rui Wang; Guang Yang; Siqi Xie; Yangjun Chen; Feifei Yang; Wei Huang; Tao Zhang; Zhihua Feng (Journal of Cleaner Production, 2023)

A joint application of semi-airborne and in-tunnel geophysical survey in complex limestone geology - Rui Liu; Huaifeng Sun; Dong Liu; Xiaoming Wang; Xiaosheng Zhou; Yu Zhao; Xinyu Zhao; Yang Yang; Guang Yang; Hanwu Sun (Bulletin of Engineering Geology and the Environment, 2023)

Heavy metals in riverine/estuarine sediments from an aquaculture wetland in metropolitan areas, China: Characterization, bioavailability and probabilistic ecological risk - Hai-Song Li; Yang-Guang Gu; Rui-Ze Liang; Ya-Su Wang; Richard W. Jordan; Liang-Gen Wang; Shi-Jun Jiang (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

A semi-analytical method for predicting train-induced vibrations considering train-track-soil and soil-pile-building dynamic interactions - Zi-Yu Tao; Chao Zou; Guang-Rui Yang; Yi-Min Wang (Soil Dynamics and Earthquake Engineering, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

LncRNA as potential biomarker and therapeutic target in glioma - Xun Xu; Yuan Liang; Ilgiz Gareev; Yanchao Liang; Rui Liu; Ning Wang; Guang Yang (Molecular Biology Reports, 2023)

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

A novel role of the mitochondrial iron-sulfur cluster assembly protein ISCU-1/ISCU in longevity and stress response - Yi Sheng; Guang Yang; Kaitlyn Casey; Shayla Curry; Mason Oliver; Sung Min Han; Christiaan Leeuwenburgh; Rui Xiao (GeroScience, 2021)

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

Comparisons of Evaluation Factors and Application Effects of the New [BQ]GSI System with International Rock Mass Classification Systems - Shen Yan-jun; Yan Rui-xin; Yang Geng-she; Xu Guang-li; Wang Shan-yong (Geotechnical and Geological Engineering, 2017)

Effects of Cold Stress on Root Growth and Physiological Metabolisms in Seedlings of Different Sugarcane Varieties - Bo Sun; Guang-Ling Liu; Thi Thu Phan; Li-Tao Yang; Yang-Rui Li; Yong-Xiu Xing (Sugar Tech, 2017)

New alkaloids from the leaves of Evodia rutaecarpa - Xiao Xia; Jian-Guang Luo; Rui-Huan Liu; Ming-Hua Yang; Ling-Yi Kong (Natural Product Research, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

A Microseismic Method for Dynamic Warning of Rockburst Development Processes in Tunnels - Guang-Liang Feng; Xia-Ting Feng; Bing-rui Chen; Ya-Xun Xiao; Yang Yu (Rock Mechanics and Rock Engineering, 2015)

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Over-expression of the MxIRT1 gene increases iron and zinc content in rice seeds - Song Tan; Rui Han; Peng Li; Guang Yang; Shuang Li; Peng Zhang; Wei-Bing Wang; Wei-Zhong Zhao; Li-Ping Yin (Transgenic Research, 2015)

Effect of Trash Addition to the Soil on Microbial Communities and Physico-Chemical Properties of Soils and Growth of Sugarcane Plants - Qing Liao; Guang-Po Wei; Gui-Fen Chen; Bin Liu; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Phytoremediation potential of Pteris vittata L. under the combined contamination of As and Pb: beneficial interaction between As and Pb - Xiao-ming Wan; Mei Lei; Tong-bin Chen; Guang-dong Zhou; Jun Yang; Xiao-yong Zhou; Xi Zhang; Rui-xiang Xu (Environmental Science and Pollution Research, 2014)

A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Integrated application of 3D seismic and microseismic data in the development of tight gas reservoirs - Rui-Zhao Yang; Zheng-Guang Zhao; Wei-Jun Peng; Yu-Bo Gu; Zhan-Gang Wang; Xi-Qin Zhuang (Applied Geophysics, 2013)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Macronutrients Absorption and Surface Runoff Losses Under Different Fertilizer Treatments in Sugarcane Field - Tian-Ming Su; Yang-Rui Li; Guang-Po Wei; Ze-Pu Jiang; Qing Liao; Shu-Biao Zhu (Sugar Tech, 2012)

Morphological and photosynthetic variations in the process of spermatia formation from vegetative cells in Porphyra yezoensis Ueda (Bangiales, Rhodophyta) and their responses to desiccation - Rui-Ling Yang; Wei Zhou; Song-Dong Shen; Guang-Ce Wang; Lin-Wen He; Guang-Hua Pan (Planta, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

OVCA1 inhibits the proliferation of epithelial ovarian cancer cells by decreasing cyclin D1 and increasing p16 - Fandou Kong; Rui Tong; Lingyu Jia; Wei Wei; Xiaoyan Miao; Xinyu Zhao; Wenping Sun; Guang Yang; Chunyan Zhao (Molecular and Cellular Biochemistry, 2011)

Inhibitor of DNA binding-1 promotes the migration and proliferation of endothelial progenitor cells in vitro - Hong Wang; Yang Yu; Rui-wei Guo; Yan-kun Shi; Ming-bao Song; Jian-fei Chen; Shi-yong Yu; Yang-guang Yin; Pan Gao; Lan Huang (Molecular and Cellular Biochemistry, 2010)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)